An Algorithm for the Multimodality Treatment of Cerebral Arteriovenous Malformations - Orlov, Kirill; Berestov, Vadim; Strelnikov, Nikolay; Moskalev, Andrey; Alshevskaya, Alina; Krivoshapkin, Alexander (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2024)
Introduction: The algorithm of multimodal treatment (MMT) of arteriovenous malformations (AVMs) combined with intent-to-cure and presurgery embolization benefits was developed. The aim was to analyze the effectiveness of the MMT compared with unimodal intent-to-cure embolization in patient groups matched concerning clinical and angiographic characteristics.Methods: A prospective cohort study of MMT effectiveness and safety was performed. To estimate differences in the total occlusion rate and complication rate of MMT compared to unimodal embolization, a 1:1 matched patient group was identified from the Russian Endovascular Neuro Society (RENS) AVM registry using the propensity score matching (EMB group). The treatment outcomes were assessed by the rate of achieving 100% AVM obliteration on follow-up angiography, morbidity, mortality, and the perioperative complication rate.Results: Complete AVM occlusion was achieved in 93.7% of patients in the MMT group vs 76.2% of patients in the EMB group (p < 0.001). A favorable clinical outcome (mRS = 0–1 at the end of follow-up) was observed in significantly more patients in the MMT group compared with the EMB group (88.9% vs 71.4%, p = 0.024). In the MMT group, the rates of intraoperative and postoperative ischemic complications were comparable to those in the EMB group, and there was a significantly lower rate of postoperative hemorrhagic complications (6.3% vs 20.6%, p = 0.035).Conclusions: Embolization as the main curative technique of the multimodal algorithm timely followed by microsurgery and radiosurgery ensures the highest clinical and angiographic efficacy of treatment and reduces the rate of disabling postoperative complications.
Keywords: Keyword; malformation